Proses Berpikir Kritis Siswa SMP dalam Menyelesaikan Masalah Matematika Ditinjau Dari Gaya Kognitif Reflektif dan Impulsif - Safri Ilman; Masriyah Masriyah; Raden Sulaiman (LP. Ma'arif Janggan Magetan, 2024)
This study is a descriptive qualitative research with the aim of describing the critical thinking process of Junior High School students in solving mathematical problems in terms of reflective and impulsive cognitive style. The subjects of this study consisted of 2 students of grade VIII junior high school with reflective cognitive style and impulsive cognitive style. The selection of both subjects also considers equivalent mathematical ability, same sex, communicative, and willing. Data collection technique is done by providing MFFT (Matching Familiar Figured Test), mathematical problem solving tasks, and interviews. Data were analyzed based on critical thinking indicators contained in FRISCO (Focus, Reason, Inference, Situation, Clarity, Overview). The results showed that the critical thinking process of both students in solving the problem is relatively the same. At the stage of understanding the second problem, students already meet the FRISCO indicator. At the stage of making a plan, reflective students already meet the FRISCO indicator, but impulsive students do not do an overview. At the stage of implementing the plan impulsive students do not pass the overview. At the last stage, namely re-examining, impulsive students do not do situation and clarity. In addition between reflective and impulsive students have different ways or solutions in solving math problems. Students with reflective cognitive style in answering a given problem can understand something as a whole, analyze it much better, and do the planning and follow the plan, so that students with reflective cognitive style can do the process of thinking critically when facing a given problem.